Noni (Morinda citrofolia L.) foliage as a phytobiotic in broiler chicken feed. (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
Poultry farming is part of the productive chain of corn, soybeansand balanced, which is one of the most important within theEcuadorian agricultural sector. Ecuadorian poultry farming hasincreased its production in recent years, unlike other types ofmeat production. The objective of the present investigationwas to determine the effect of the addition of noni (Morindacitrofolia L.) foliage levels on the productive performance ofBroiler chickens. The work was carried out in the "Cañales"Campus of the Mocache Canton, Los Ríos province. 160 BroilerCobb 500 chickens were used, distributed in a completelyrandomized design with 4 treatments, 5 repetitions each, with8 animals as the experimental unit. The evaluated treatmentsare T1 (Control; Commercial Balanced); T2, T3 and T4 (0.5, 1 and1.5% respectively of Noni foliage flour). No statisticaldifferences were found in relation to the productiveparameters between the means of Tukey treatments (P≤0.05),however in the cost-benefit relation, 0.5% of Noni foliagepresented the best value ($ 1.27), which means that for everydollar invested, a profit of 0.27 cents was obtained, with aprofitability of 27.49% and a mortality of 2.5%. While thecontrol treatment obtained a value of $ 1.12; a profitability of11.71% and a mortality of 5%.